Effects of agrotechnical factors on the quality and quantity of yield in winter wheat production - Magyar, Zoltán; Pepó, Péter; Gyimes, Ernő (Acta Agraria Debreceniensis, 2020)
The present study was conducted to determine the effect of basic agrotechnical factors on the yield and quality of winter wheat. Two experiments were set in 2017/2018 growing season, where we studied the influence of different forecrops, fertilizing treatments and cultivars. 204 samples were measured with Single Kernel Characterization System and NIR grain analyser to determine protein (NIR-P), wet gluten (NIR-WG), Hardness Index (HI), kernel weight (KW) and kernel diameter (KD). Fertilizing had a significant effect on yield, KW, HI, NIR-P and NIR-WG, except KD. N90PK dosage was enough to realize yield potential for 6 out of 9 cultivars, but considering protein content N150PK dosage was needed. The forecrop had no significant influence on yield, KW, KD or HI, however sweet corn as previous crop had significant improving effect on NIR-P and NIR-WG compared to sunflower as forecrop. According to our data of correlation analysis, no negative relationship was found between yield and NIR-P, however HI was in medium positive correlation with NIR-P. The variety Vyckor had the highest yield, but in quality aspect, the highest NIR-P and NIR-WG values belonged to KG Kunhalom variety.